COMPUTATIONAL TOOLS FOR SIMULATING SURFACE WAVE ON VARIOUS TOPOGRAPHY - Fernando, Felix
Shallow water equation (SWE) has been widely used to study the occurrence of surface waves, and the use of SWE allows fairly accurate and easy simulation for various real cases of surface waves. In this research, a computational tool will be developed to perform simulations with SWE with an interface that makes it easier for users to operate the computational tool. The developed computational tool will be able to overcome the challenges of simulation over various topographies, enabling precise modeling of wave interactions with diverse topographic structures. In its development, the computational tool will utilize Godot which is a game engine. Integrating Godot as a game engine provides additional advantages by providing a user-friendly user interface and attractive visualizations. Thus, this tool is not only a platform for scientific studies but also can be widely used by various groups, including researchers, educators, and students, to better understand the surface wave phenomenon.